2005
DOI: 10.1111/j.1365-2710.2005.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Does pulmonary rehabilitation give additional benefit over tiotropium therapy in primary care management of chronic obstructive pulmonary disease? Randomized controlled clinical trial in Hong Kong Chinese

Abstract: Tiotropium therapy has improved health outcomes in COPD patients in primary care settings. A 6 weekly PRP did not give any additional benefits in patients already given tiotropium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Lindsay et al 35 reported insufficient data with which to calculate effect size/ SMD. Berry et al 38 reported estimated means for repeated measures analysis (adjusted for age and gender) for QOL measures and physical function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindsay et al 35 reported insufficient data with which to calculate effect size/ SMD. Berry et al 38 reported estimated means for repeated measures analysis (adjusted for age and gender) for QOL measures and physical function.…”
Section: Resultsmentioning
confidence: 99%
“…Exercise and psychological interventions 29 Wijkstra et al 30 Guell et al 31 Kayahan et al 32 Emery et al 33 Ries et al 34 de Godoy et al 6 Lindsay et al 35 de Godoy and de Godoy 5 Norweg et al 36 de Blok et al 37 Berry et al 29 Wijkstra et al 30 Guell et al 31 Kayahan et al Guell et al 31 Kayahan et al 32 Emery et al…”
mentioning
confidence: 99%
“…In contrast, post-resistance exercise quality of life was shown to be better than baseline quality of life (28) and post-standard treatment quality of life (29) (1 analysis each). The effects that combining a given rehabilitation program with creatine, (13) tiotropium, (17,30) or hypertonic saline (31) had on quality of life did not differ from those observed when the rehabilitation program was used in isolation. Duiverman et al (15) compared the use of rehabilitation programs in isolation with the that of those same programs in combination with noninvasive ventilation and found that the latter improved quality of life in 2 of 4 analysis examining the degree of fatigue.…”
Section: Symptomsmentioning
confidence: 95%
“…There were no significant differences between patients who underwent the standard treatment and those who performed resistance exercises regarding pulmonary function, (29) although pulmonary function improved in both groups of patients. Combining rehabilitation programs with ventilation-feedback training, (14) tiotropium use, (30) or noninvasive ventilation (15) was ineffective in improving the pulmonary function of patients with moderate to very severe COPD in relation to that of those who exclusively underwent a rehabilitation program.…”
Section: Pulmonary Functionmentioning
confidence: 98%
See 1 more Smart Citation